2014
DOI: 10.19104/jbtr.2014.107
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Paracrine Factors in Vascular Repair and Regeneration

Abstract: Mesenchymal stem cell therapy show great optimism in the treatment of several diseases. MSCs are attractive candidates for cell therapy because of easy isolation, high expansion potential giving unlimited pool of transplantable cells, low immunogenicity, amenability to ex vivo genetic modification, and multipotency. The stem cells orchestrate the repair process by various mechanisms such as transdifferentiation, cell fusion, microvesicles or exosomes and most importantly by secreting paracrine factors. The MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 115 publications
(140 reference statements)
0
62
0
Order By: Relevance
“…Uterus with intrauterine adhesions characterized by thin‐walled telangiectatic vessels indicated that angiogenesis played a significant role in the endometrium restoration . Taken together, these results indicate that PGS/BMSCs facilitate regeneration of uterus due to the increase of vascularity which promotes the approach to nutrients and hormones through the secreting various growth factors, including bFGF and VEGF . In addition to inducing angiogenesis, BMSCs may facilitate tissue repair through secreting TGF‐β1 which is helpful to a resurgent microenvironment by weakening apoptosis, abating immune responses .…”
Section: Discussionmentioning
confidence: 99%
“…Uterus with intrauterine adhesions characterized by thin‐walled telangiectatic vessels indicated that angiogenesis played a significant role in the endometrium restoration . Taken together, these results indicate that PGS/BMSCs facilitate regeneration of uterus due to the increase of vascularity which promotes the approach to nutrients and hormones through the secreting various growth factors, including bFGF and VEGF . In addition to inducing angiogenesis, BMSCs may facilitate tissue repair through secreting TGF‐β1 which is helpful to a resurgent microenvironment by weakening apoptosis, abating immune responses .…”
Section: Discussionmentioning
confidence: 99%
“…Bone is a highly-vascularized tissue and for bone regeneration an adequate blood flow is required to provide sufficient supply of nutrients and oxygen to the cells 52 , 53 . In response to angiogenic signals found in conditioned media obtained from BM MSC cultures, endothelial cells may form capillary like structures 54 . In our study, conditioned medium from BM MSC seeded onto OC/OPN-enhanced collagen gels increased the tube formation of endothelial cells, when compared with the control, by increasing the number of total capillary tubes and branch points formed.…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies indicated that MSCs had the beneficial effects on vascular injury [ 11 , 12 ]. MSCs orchestrate the repair process of injured vessels by various mechanisms such as transdifferentiation, microvesicles or exosomes, and secreting cytokines [ 13 , 14 ]. MSCs can directly differentiate into endothelial cells to participate in angiogenesis [ 15 ] or migrate and home to the injured large blood vessel for vascular repair by regulating various cell cytokines, such as transforming growth factor beta (TGF- β ), vascular endothelial growth factor (VEGF), and intercellular cell adhesion molecules (ICAM) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%